Triple Helix dalam Aksi: Strategi Kemitraan Kampus-Industri untuk Inovasi Berkelanjutan - Citra Dwi Palenti; Ririn Gusti; Aflin Julianto; Pani Aswin (Unri Conference Series: Community Engagement, 2025)
Education in Indonesia plays a strategic role in human development. The educational process can change behavior, improve skills, foster religious approaches, develop the potential for awareness, and become independent individuals. This study aims to determine the potential for campuses to contribute to sustainable innovation through a triple helix approach. The method used is a quantitative field research approach involving campuses, industry, and the government. The results show that research contributions to industry (average = 4.2; standard deviation = 0.7) and knowledge transfer (average = 4.0; standard deviation = 0.6) are in the high category. In the industrial aspect, support for innovation programs received a fairly high score (average = 3.9; standard deviation = 0.8), while investment obligations in research were at a moderate level (average = 3.7; standard deviation = 0.9). Furthermore, pro-innovation regulations (Mean = 3.8; Standard Deviation = 0.7) and funding facilitation (Mean = 3.6; Standard Deviation = 0.8) are in the moderate category and Collaboration between actors in the triple helix model shows good results. The level of synergy between campuses and industry (Mean = 4.1; Standard Deviation = 0.6) and the sustainability of joint programs (Mean = 4.0; Standard Deviation = 0.7) are in the good category. Based on the research results that have been obtained, the triple helix model is a collaborative model design that can be used in human development. It is found that industrial collaboration supports research in the world of academic campuses plays a role in research and practical value for the industrial world. Furthermore, collaboration between actors shows good results involving not only campuses, industry, and government, but also the community as end users. The government plays a role as a facilitator and driver that supports the growth of innovation.